2022
DOI: 10.3389/feduc.2022.1044608
|View full text |Cite
|
Sign up to set email alerts
|

School attendance and school absenteeism: A primer for the past, present, and theory of change for the future

Abstract: School attendance and school absenteeism have been studied for over a century, leading to a rich and vast literature base. At the same time, powerful demographic, climate, social justice/equity, and technological/globalization forces are compelling disparate stakeholders worldwide to quickly adapt to rapidly changing conditions and to consider new visions of child education for the next century. These overarching forces are utilized within a theory of change approach to help develop such a vision of school att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 129 publications
(124 reference statements)
0
17
0
Order By: Relevance
“…Fundamental variations to schooling caused by health-related crises, climate change, demographic shifts, and technology, among other key alterations, have also raised new implications for community-level data collection and analysis (Kearney et al, 2022). New questions have emerged to understand further the intersection of communities and schools, especially as it relates to school attendance.…”
Section: Discussionmentioning
confidence: 99%
“…Fundamental variations to schooling caused by health-related crises, climate change, demographic shifts, and technology, among other key alterations, have also raised new implications for community-level data collection and analysis (Kearney et al, 2022). New questions have emerged to understand further the intersection of communities and schools, especially as it relates to school attendance.…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, school non-attendance has long been in focus (Reid, 2008(Reid, , 2012(Reid, , 2016Ricking, 2003;Kearney et al, 2022). Different concepts are used in the international literature, such as 'truancy', 'school absenteeism', 'persistent school absenteeism', and 'school refusal behaviour'.…”
Section: Introductionmentioning
confidence: 99%
“…According to the United Nations Educational, Scientific and Cultural Organization (UNESCO), around 17% of children worldwide do not attend school, with many of these children unable to do so due to barriers such as gender, disability, ethnicity, or social determinants of health, among other reasons (Kearney et al, 2022; UNESCO Institute for Statistics, 2019). Chronic school absenteeism, often defined as missing 10% or more of the school year, can affect students of all ages.…”
mentioning
confidence: 99%
“…Behavioral and mental health specialists should prioritize these to optimize a student's health and academic performance. Schools are places for academic and socio‐emotional development, and previous studies have shown that better attendance is correlated with numerous positive outcomes, including better test performance and lower dropout rates (Kearney et al, 2022; Rhode Island Kids Count, 2023). In addition, schools often provide access to safe spaces and food that some youth may not have at home.…”
mentioning
confidence: 99%
See 1 more Smart Citation